A New Metasurface Structure for Bandwidth Improvement of Antenna Array - Lan Ngoc Nguyen (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, the design of an antenna array with enhanced bandwidth is presented. The antenna array includes 16 elements (4 x 4) based on RT5880 with height of 1.575 mm, dielectric constant of 2.2 and loss tangent of 0.0009 and it is yielded at the central frequency of 5.8 GHz for Wireless Local Area Network (WLAN) applications. In addition, in order to enhance bandwidth for antenna, the paper proposes a new metasurface. The metasurface, which is a lattice of 3 x 3 cells, is printed on a substrate of FR4 (h = 1.6 mm, ɛr = 4.4, and tanδ = 0.02) and it acts as an artificial magnetic conductor reflector. The final prototype with an overall dimension of 123 x 120 x 3.315 mm3 was fabricated and measured. The antenna witnesses an impedance bandwidth of 5.1-7.5 GHz at -10 dB (41%) and a peak gain of 17.65 dBi for measurement. The simulation results are confirmed by measurement ones to verify the performance of the proposed antenna.